Impact of Educational Messaging via Social Media Platforms TikTok and WhatsApp on Stunting Awareness among Adolescent Females in Polewali Mandar District, Indonesia - Niswa, Nurun; Suriah, Suriah; Syafar, Muhammad; Thaha, Ridwan; Masni, Masni (Journal of Neonatal Surgery, 2025)
Background: Stunting remains a significant public health issue in Indonesia, with a high prevalence in various regions, including Polewali Mandar Regency. The use of social media as a health education tool has been increasing, especially among adolescent girls. TikTok and WhatsApp are two widely used platforms that have the potential to raise awareness about stunting. Objective: This study aims to analyze the influence of stunting awareness educational messages delivered through TikTok and WhatsApp on the knowledge, perceptions, and attitudes of adolescent girls at SMAN 1 and SMAN 3 in Polewali Mandar Regency. Methods: This research employs a quasi-experimental design with a pre-test and post-test approach in two intervention groups: the TikTok group and the WhatsApp group. The TikTok group consists of adolescent girls from SMAN 1 Polewali Mandar, while the WhatsApp group consists of adolescent girls from SMAN 3 Polewali Mandar. The total sample size in this study is 206 respondents, evenly distributed with 103 respondents in each group. The sample selection was conducted using the Simple Random Sampling technique. Data analysis was performed using the Paired Sample T-Test, Wilcoxon Signed Rank Test, Independent Sample T-Test, and Mann-Whitney U Test with a significance level of 0.05. Results: There was a significant increase in knowledge, perceptions, and attitudes of adolescent girls after the educational intervention using TikTok and WhatsApp (p-value < 0.05). The group receiving education through TikTok showed a greater improvement compared to the group receiving education through WhatsApp. Conclusion: TikTok proved to be more influential than WhatsApp in enhancing knowledge, perceptions, and stunting awareness attitudes among adolescent girls. Although WhatsApp also had a positive impact, its effect was not as strong as TikTok. These findings suggest that social media can be a powerful tool in health campaigns targeting adolescent girls.